Religious phenomenon, subject and types - Zatov, K.A.; Borbassova, K.M.; Aldiyarova, Zh.E. (ҚазҰУ Хабаршысы. Дінтану сериясы, 2019)
The article analyzes one of the actual problems of modern sociology and psychology of religion – the phenomenon of religiosity. Despite the abundance of scientific articles, religiosity is the most difficult problem for the researcher, since its content and form are modified in accordance with the spiritual needs of the individual and society. And this circumstance requires a rethinking of the research problem, revision of theoretical principles and methodological principles. The authors of the article emphasize the interdisciplinary nature of the problem and support the system-structural and functional approaches to its study. Focusing on the concept of types of religiosity developed in psychology and sociology of religion, the authors describe the manifestations of religiosity in Kazakhstan society. This allows the authors to highlight positive, authoritarian and destructive types of religiosity. The positive type of religiosity is characterized by openness, the ability to dialogue and tolerance. The authoritarian type is characterized by group isolationism, insensitivity to alternative views, critical attitude of the religious tradition of other religious communities. Destructive religiosity generates negative religious feelings in the behavior and consciousness of believers – an irresistible sense of sinfulness, fear and other various phobias. The conclusions and results of the authors of the article can contribute to the further development of theoretical and practical aspects of the phenomenon of religiosity.